(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the impact of free market entry for participants on the availability of goods and services from both theoretical and practical perspectives. The study highlights factors such as increased competition, expansion of production volumes, price reduction, and broader satisfaction of consumer needs under conditions of free entry. The research substantiates the role of free market mechanisms in enhancing economic efficiency and social welfare.